肾上腺区巨大肿瘤合并瘤栓的诊断与治疗 (Beijing Da Xue Xue Bao Yi Xue Ban, 2019)
OBJECTIVE: To summarize the experience of diagnosis and operation related to massive adrenal area tumor with venous tumor thrombus in clinic. METHODS: From October 2017 to March 2019, a total of 8 cases of massive adrenal area tumor (>7 cm) with venous tumor thrombus were admitted at Peking University Third Hospital including 5 males and 3 females with mean age 50.6 years (31-62 years). There were 6 cases on the right side and 2 cases on the left side. The first symptoms included abdominal discomfort, hypertension, Cushing syndrome and abnormal menstruation; special past history included cirrhosis and lung cancer. Computed tomography (CT) and routine endocrine hormone tests were examined. Preoperative imaging confirmed 5 cases masses with tumor thrombus in inferior vena cava (IVC) and 1 case with tumor thrombus in left renal vein. Two cases presented with tumor thrombus in central adrenal vein were found intraoperatively. Open adrenalectomy and thrombectomy were performed in 4 cases of right side complicated with high tumor thrombus of inferior vena cava. Laparoscopic adrenalectomy and thrombectomy were performed in 3 cases, including 2 cases on the right and 1 case on the left. The case with tumor thrombus in left renal vein gave up operation. The patients were followed up with outpatient and telephone. RESULTS: The mean size of the tumor was 8.9 cm (7-11 cm), the mean operative time was 319 min (120-510 min), while the estimated blood loss was 629 mL (50-1 200 mL). Intraoperative blood transfusion was required in 2 cases and 1 case encountered wound infection. The pathological types included pheochromocytoma, adrenocortical carcinoma, adrenal metastases of haptic carcinoma, and leiomyosarcoma. The case with left lung carcinoma who underwent left pneumonectomy one month before was highly suspected adrenal metastases of lung carcinoma. Tumor thrombus of pheochromocytoma was combined with blood thrombus. Capsule of adrenocortical carcinoma was fragile in adrenocortical carcinoma. Abundant blood supply existed in adrenal metastases. The leiomyosarcoma had unabundant blood supply and invaded IVC to form tumors thrombus. The mean follow-up time was 8.4 months (1-15 months). One case with adrenocortical carcinoma died after 1 year in the follow-up. CONCLUSION: We present the rare cases of different pathological types of massive adrenal tumors with tumor thrombus extending into the IVC extension or other vein. Preoperative diagnosis needs comprehensive evaluation and perfect preoperative preparation. Surgery is difficult and varied. Open approach as well as retroperitoneal laparoscopic approach is feasible.